A new species of the genus Mawenzhena Alexis & Delpont (Coleoptera: Scarabaeidae: Cetoniinae: Goliathini) from South Korea - Kim, Jihoon; Jung, Sunghoon (Zootaxa, 2019)
Genus, Mawenzhena Alexis & Delpont (Coleoptera: Scarabaeidae: Cetoniinae: Goliathini), is reported from Korean Peninsula for the first time with the description of a new species, Mawenzhena Koreana J.H. Kim & Jung, sp. nov. Description of the new species, diagnosis for the members of the genus and a key to the Korean genera of the subtribe Coryphocerina are provided together with photographs of adult specimens and male genitalia.